Emerging Role and Mechanism of circRNAs in Pediatric Malignant Solid Tumors - Shen, Qiyang; Liu, Xingyu; Li, Wei; Zhao, Xu; Li, Tao; Zhou, Kai; Zhou, Jianfeng (Frontiers in Genetics, 2022)
Circular RNAs (circRNAs) are non-coding RNAs with covalent closed-loop structures and are widely distributed in eukaryotes, conserved and stable as well as tissue-specific. Malignant solid tumors pose a serious health risk to children and are one of the leading causes of pediatric mortality. Studies have shown that circRNAs play an important regulatory role in the development of childhood malignant solid tumors, hence are potential biomarkers and therapeutic targets for tumors. This paper reviews the biological characteristics and functions of circRNAs as well as the research progress related to childhood malignant solid tumors.